The Filipino Migration Experience : Global Agents of Change - Roces, Mina, 1959- (Book collections on Project MUSE., 2021)
"This book documents the way Filipino migrants from the 1970s-2018 have become agents of change. Migrants critiqued institutions such the family and definitions of the feminine, they transformed social mores and inspired transnational business ventures, they altered the host countries through advocacy, and they revolutionized the homeland through diasporic philanthropy"--